Mineralogical and physico-chemical properties of the Cretaceous shales of the Calabar Flank, south-eastern, Nigeria: Implication for paleo-weathering conditions, provenance and industrial applications - Christopher I. Adamu; Oluwaseye P. Oyetade; Azubuike S. Ekwere; Ebenezer A. Kudamnya; Kehinde I. Adebayo; Idara A. Uyok; Therese N. Nganje (Solid Earth Sciences, 2022)
The Physico-chemical and mineralogical properties of the Cretaceous shales of Calabar Flank southeastern Nigeria were examined for their Provenance, Paleo-weathering Conditions and Industrial Applications. Twenty samples of shale from Ekekpon and Nkporo Formations were analysed using X-Ray Fluorescence, X-ray diffraction (XRD), scanning electron microscopy (SEM) and geotechnical techniques. Results from the major oxides of elements revealed that the Nkporo Shale is enriched with SiO2 > Al2O3 > LOI > Fe2O3 > SO3 while the Ekepkon shale is also enriched in SiO2 > Al2O3 > LOI > Fe2O3 > CaO > K2O. The XRD revealed kaolinite as the major clay mineral, while other non-clay minerals are quartz, vallerite, mica, nacaphite, sodalite. The SEM shows that the Ekepkon Shale is enriched in calcium. The correlation matrix revealed SiO2 resides more in the quartz phase of the Nkporo Shales, while in the Ekekpon Shale the SiO2 is associated with the clay. The element ratios and discrimination diagrams revealed that the provenance of the shales is of intermediate to mafic igneous rocks and a tectonic setting of continental to oceanic arcs. The presence of kaolinite in the Nkporo Shale with the chemical index of alteration (CIA) values ranging from 83.58 to 96.93, indicated that the shale is derived from intensive chemical weathering in the source area. The low CIA values (37.90–76.96) in Ekenkpon Shale is attributed to CaO and calcium enrichment in the shale and the shale contains high quartz and kaolinite therefore the shale is suggested to have been derived from an intermediate to intense weathering activities in the source area. The geotechnical properties revealed that both shales are suitable for ceramic and refractory industries. The Ekenkpon Shale will be suitable for use as filling material and as raw material in cement industries. However, the shales do not meet the specifications for paper and rubber production due to the high contents of iron oxide, lime, magnesia, potash and soda.